Lysine Requirements of Healthy Pregnant Women are Higher During Late Stages of Gestation Compared to Early Gestation. Issue 1 (25th January 2018) - Payne, Magdalene; Stephens, Trina; Lim, Kenneth; Ball, Ronald O; Pencharz, Paul B; Elango, Rajavel
Abstract: Background: Lysine is the first limiting amino acid in cereal proteins and is found mainly in animal-derived products. Current Dietary Reference Intake (DRI) recommendations extrapolate lysine requirements during pregnancy from nonpregnant adult data, and may underestimate true requirements. Objective: Our objective is to define a quantitative lysine requirement in healthy pregnant women and to determine whether requirements vary between 2 phases of gestation. Methods: Fourteen pregnant women in early (12–19 wk) and 19 women in late (33–39 wk) gestation were studied using the indicator amino acid oxidation technique. Individual lysine intakes (6–84 mg · kg −1 · d −1, deficient to excess) were tested on each study day as a crystalline amino acid mixture based on egg protein composition. Isonitrogenous diets maintained protein intake at 1.5 g · kg −1 · d −1 and calorie intake at 1.7 times resting energy expenditure during each study day. Phenylalanine and tyrosine intakes were held constant across all lysine intakes. Breath and urine samples were collected at baseline and isotopic steady state. Lysine requirements were determined by measuring the oxidation of L-[1- 13 C]-phenylalanine to 13 CO2 (F 13 CO2 ). Biphase linear regression crossover analysis was used to determine a breakpoint (which represents the estimated average requirement, EAR) in F 13 CO2 . Results: The EAR for lysine during early gestation was determined to be 36.6 mg · kg −1 · d −1 ( R 2 = 0.484, upper 95% CI = 46.2 mg · kg −1 · d −1 ), similar to an earlier adult requirement of 36 mg · kg −1 · d −1 . The EAR for lysine during late gestation was determined to be 50.3 mg · kg −1 · d −1 ( R 2 = 0.664, upper 95% CI = 60.4 mg · kg −1 · d −1 ), 23% higher than the current pregnancy DRI EAR recommendation of 41 mg · kg −1 · d −1 . Conclusions: Our results suggest that lysine requirements are higher during late gestation compared to early gestation, and that current dietary lysine recommendations during late stages of pregnancy may be underestimated. The results have implications for populations consuming cereal-based diets as their primary source of protein. This trial was registered at clinicaltrials.gov as NCT01776931.